ANALISIS PENGENDALIAN KUALITAS PRODUK KEBAYA DI UKM MARSADA SONGKET KEBAYA DAN TAILOR - Giro, Monica; Sumantika, Arsyad (Computer Science and Industrial Engineering, 2024)
Marsada Songket Kebaya and Tailor is a business engaged in convection in the form of services that are still classified as micro that produce products in the form of kebaya and songket. The purpose of this study is to identify the factors that cause defective products in the production process, find out the types of defects that occur and make recommendations for improvement. The methods used are Define, Measure, Analyze, Improve, Control (DMAIC) and Failure Mode and Effect Analysis (FMEA). Based on the results of the study, the defects that occurred in Marsada Songket kebaya and Tailor were sewing defects, accessories defects and fabric defects. The recommendation for improvement is to set SOPs in accordance with work standards so that they can be carried out more efficiently and effectively.